The efficacy and safety of hybrid ablations for atrial fibrillation, assessed using implantable ECG recorders and sequential magnetic resonance imaging. (25th November 2020) - Osmancik, P; Herman, D; Kacer, P; Rizov, V; Vesela, J; Prochazkova, R; Karch, J; Budera, P
Abstract: Background: Treatment strategies for patients with non-paroxysmal atrial fibrillation (AF) still do not provide satisfactory results. In pursuit of better results, other approaches, such as the hybrid ablation (i.e., thoracoscopic epicardial ablation followed by catheter ablation), have been used. The accurate data regarding the efficacy and safety of the procedure are still limited. Purpose: To determine the procedural safety, and the mid-term efficacy of hybrid ablation. Methods: Patients with non-paroxysmal AF were included. They underwent thoracoscopic, off-pump ablation using the COBRA Fusion radiofrequency system, followed by a percutaneous catheter ablation (2.6±1.0 mo after surgery). Sequential cerebral magnetic resonance imaging (MRI) was done (1 day before and 3–5 days after surgery) to look for new ischemic lesions in the brain. Implantable loop recorders (ILR) were implanted 1–3 days after the thoracoscopic procedure. Rhythm outcomes were defined as (1) AF-free OFF survival (i.e., no single episode of AF or atrial tachycardia (AT) lasting >30 sec as assessed using ILR, remaining OFF anti-arrhythmic drugs (AADs) and without a redo ablation or cardioversion), (2) AF-free ON survival (i.e., recurrence of AF or AT, however, AF freedom with no more AF/AT episodes >30 sec was achieved through re-initiation AADs, re-ablation, or cardioversion), and (3) rhythm control survival (repeated self-terminated paroxysms of AF/AT despite AADs, re-ablation, or cardioversion). Rate control strategy (i.e. the presence of AF with no more attempts for SR reinitiation) was considered as failure of the procedure. Results: Sixty patients were enrolled, 37 (62%) were men, the mean age was 62.6±10.5 years, 29 (48%) with long-standing persistent AF. Thoracoscopic ablation was successfully performed in 56 (93.3%) patients, and significant complications occurred in 7 (11.8%) patients. Fifty-three patients (88.3%) underwent a pre- and 47 underwent a control postoperative cerebral MRI. Chronic ischemic brain lesions were present in 36 (68%) patients on the pre-operative MRI. New ischemic brain lesions on the post-operative MRI were seen in 19 (40%) patients, 18 of whom were without neurological symptoms, 1 patient had a manifest stroke. Catheter ablations were carried out in all 60 patients without complications. The mean follow-up was 22.9±10.3 months. AF-free OFF survival was present in 53.4% at 1 and in 41.5% at 2 years. AF-free ON survival was present in 72% at 1 year and 62% at 2 years. Rhythm control survival was present in 91% at 1 year and 89% at 2 years. Only 9%, or 11% of patients were on rate control at 1 and 2 years, resp. Conclusions: Hybrid ablation presents an effective treatment strategy for patients with non-paroxysmal AF. The thoracoscopic part of the hybrid ablation procedure is accompanied by a high risk of silent cerebral ischemia, which should be considered in patients referred to this procedure. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Research grant of the Ministry of Health of the Czech Republic, Nr. 16-32478A